Private Community Assistance in Antenatal Care at High Risk Pregnant Women in Public Health Center of Jelakombo Jombang: Pendampingan Kader dengan Kunjungan Antenatal Care (Anc) Ibu Hamil Risiko Tinggi Di Puskesmas Jelakombo Jombang - Rahayu, Dewi Taurisiawati; Askabulaikhah, Askabulaikhah (Universitas Muhammadiyah Sidoarjo, 2020)
Maternal Mortality Rate (MMR) in 2012 was 359 per 100,000 live births. In 2015, based on 2015 SUPAS data, both MMR and IMR showed a decrease (MMR 305 / 100,000 KH; IMR 22.23 / 1000 KH). The purpose of this study was to determine the effect of the implementation of cadre assistance on antenatal care (ANC) visits of high-risk pregnant women in Jelakombo Jombang.This type of research is correlational with the Cross Sectional approach. Population 63 high risk pregnant women, sample 54 high risk pregnant women. The study was conducted from 03 to 17 July 2019. The independent variable was the implementation of cadre mentoring and the dependent variable was the ANC visit. The side technique used is simple random sampling. Data obtained from ANC questionnaire and MCH Book Checklist. Data analysis using the Mann Whitney test.The results of the implementation of cadre mentoring were quite good as many as 32 respondents (59.3%). ANC visits were mostly active in visiting ANC, namely 40 respondents (74.1%). Implementation of pregnant women by good cadres 32 respondents, most respondents 32 high risk mothers (93.8%) actively visited ANC. Statistical test results using the Mann-Whitney U test obtained r = 0,000 (r<0.05) so that Ho was rejected means that it was concluded there was a correlation between the Implementation of Cadre Assistance with ANC Visit of Risti Pregnant Women at Jelakombo Health Center in Jombang Regency.